2018
DOI: 10.1080/21691401.2017.1423494
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoparticles triggered the induction of ROS-mediated cytoprotective autophagy in cancer cells

Abstract: There is a close relationship between autophagy and apoptosis during cancer cell death. We used chitosan nanoparticles (CS NPs) to explore the effects of internalized NPs on the induction of autophagy and to confirm the role of autophagic responses elicited by nanomaterials on the tumour cell's fate. CS NPs at nontoxic concentrations ranging from 10-100 μg/mL triggered the induction of autophagy. With the addition of CS NPs, the aggregation of endogenous LC3 was significantly enhanced and acidic autophagic bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 27 publications
4
22
1
Order By: Relevance
“…The molecular mechanism underlying autophagy has been extensively investigated in recent years. The mitochondrial antioxidant Mito-TEMPO (mitochondrial-targeted SOD mimetic) enhanced SOD2 activity but not SOD2 levels, significantly suppressed the 5-ALA-PDT-mediated increase in autophagy level, and consistent with many studies revealed that ROS can induce autophagy [34] , [35] , [36] .…”
Section: Discussionsupporting
confidence: 82%
“…The molecular mechanism underlying autophagy has been extensively investigated in recent years. The mitochondrial antioxidant Mito-TEMPO (mitochondrial-targeted SOD mimetic) enhanced SOD2 activity but not SOD2 levels, significantly suppressed the 5-ALA-PDT-mediated increase in autophagy level, and consistent with many studies revealed that ROS can induce autophagy [34] , [35] , [36] .…”
Section: Discussionsupporting
confidence: 82%
“…Literature review showed several contradictory results regarding Chit NPs effect on cellular ROS production. One study suggested that Chit NPs had an inhibitory activity (Bor et al, 2016), two studies reported no Chit NPs effect (Omar Zaki et al, 2015;Arora et al, 2016) and three reported a stimulating effect (Hu et al, 2011;Sarangapani et al, 2018;Wang et al, 2018) on basal ROS cellular production. Concerning the polymer, same conflicting results were also found (Arora et al, 2016;Salehi et al, 2017;Sarangapani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…ROS plays an complicated role in cancer process, it can not only mediated cancer cytoprotective autophagy [35] but also directly induce apoptosis. Additionally, we also found that the combination of DOX and Se@SiO 2 could augment the antitumour efficacy of DOX.…”
Section: Discussionmentioning
confidence: 99%